Comparative analysis of pollen morphology at three flowering stages of Trimezia martinicensis (Jacq.) Herb. (Iridaceae), an invasive species in Indonesia - Alda Wydia Prihartini Azar; Isnaeni Nur Ardianti; Hasna Dyah Kusumardani; Sri Lestari; Riska Desi Aryani (Bioma, 2025)
Pollen morphology provides critical insights into plant reproduction, taxonomy, and evolutionary relationships. This study investigates pollen development in Trimezia martinicensis (Iridaceae), an invasive alien species in Indonesia, across three flowering stages: closed bud, developed bud, and mature flower. Vegetative and floral traits were documented alongside stage-specific palynological analyses. Pollen grains were examined under light microscopy to assess changes in orientation, shape, aperture, and exine architecture. Results revealed distinct morphological transitions, including spheroidal grains with monocolpate apertures at early stages, progressing to more rounded forms with refined wall structures in mature flowers. These findings highlight the dynamic nature of pollen morphology during anthesis and underscore its relevance for reproductive biology, taxonomy, and management of IAS in Indonesia.